Practice of Thudong in Indonesia: Evidence of Actualization on Pancasila Values through Religious Rituals - Suroyo Suroyo; Bima Maulana Putra (Badan Pembinaan Ideologi Pancasila, 2024)
The practice of Thudong, a form of spiritual journey undertaken by Buddhist monks, has gained popularity in Indonesia in recent years. This study aimed to explore the extent to which Thudong practitioners actualize Pancasila values, which are the foundational principles of the Indonesian state, through their religious rituals. This qualitative research employed a case study design, with six Thudong practitioners selected as the subjects of the study. Data was collected through semi-structured interviews and participant observation of the practitioners’ religious rituals. The data was analyzed using thematic analysis. The findings of the study revealed that Thudong practitioners in Indonesia actively engage in religious rituals that reflect the Pancasila values. The practitioners’ dedication to their spiritual journey was characterized by a deep sense of respect for their fellow human beings and the environment. They demonstrated a strong commitment to social justice, equality, and tolerance towards different religious and cultural practices. The study also found that Thudong practitioners in Indonesia have a unique approach to their spiritual journey, which combines Buddhist teachings with local cultural practices. This fusion of traditions allows for a richer and more diverse religious experience, enabling practitioners to better actualize Pancasila values. In conclusion, this study provides evidence that Thudong practice in Indonesia serves as a means of actualizing Pancasila values through religious rituals. The findings suggest that Thudong practice has the potential to contribute positively to the development of a more just and tolerant society in Indonesia